Chemotherapy regimen checks performed by pharmacists contribute to safe administration of chemotherapy. (January 2017) - Suzuki, Shinya; Chan, Alexandre; Nomura, Hisanaga; Johnson, Philip E; Endo, Kazushi; Saito, Shinichiro
Background: Computerized provider order entry (CPOE) has been developed and implemented within cancer center hospitals nationwide in Japan. To ensure that high-quality services are routinely provided by oncology pharmacists, this study was designed to evaluate the interventions through reviewing the orders that are generated by CPOE. Methods: The objective of this retrospective chart review was to evaluate how pharmacists contributed to safe cancer treatment using paper-based pharmacy records. Data were collected from a total of 35, 062 chemotherapy regimens for 18, 515 outpatients between January and December 2013. Results: Of these 35, 062 chemotherapy regimens, the rate of pharmacists' interventions was 1.1% ( n  = 408). Among them, 53.1% (217/408) of the chemotherapy prescriptions were modified due to pharmacist interventions. The reasons for interventions included "changes in the chemotherapy regimen were unclear" in 49.5%, "physicians' prescription errors" (22.0%), "pharmacist suggestions to improve chemotherapy" (15.1%), and "finding differences between physicians' chemotherapy records and their chemotherapy prescriptions" (13.2%). The top three reasons for the 217 prescription modifications due to pharmacist interventions were "finding prescription errors" (34.5%), "reasons for change in the chemotherapy regimen were unclear" (32.7%), and "finding differences between physicians' chemotherapy records and their chemotherapy prescriptions" (28.5%). Conclusion: The computer could not evaluate chemotherapy protocols or adjust doses of anticancer medicines according to patients' conditions. Therefore, oncology pharmacists should continue to ensure safe and appropriate administration of cancer chemotherapy.